42.1k views
5 votes
What is the solution to the equation ^3sqrt m-4- ^3sqrt 2m+8=0

A. m= -24
B. m= -12
C. m= -6
D. m= -4

User Anroots
by
4.5k points

2 Answers

4 votes

Answer:

B

Step-by-step explanation:

E2020

User Jessica Lingmn
by
5.5k points
5 votes
The correct answer is: [B]: " m = -12 " .
________________________________________________________

Step-by-step explanation:
_________________________________________________________
Given the equation:

" ³√(m − 4) − ³√(2m + 8) = 0 " ; Solve for "m" ;

_________________________________________________________

We start by rewriting the terms in the equation:
_________________________________________________________
Note the following property of exponents:
_________________________________________________________

" a ⁽ ˣ / ʸ⁾ = ʸ√(aˣ) ; { y
\\eq 0 } " ;
_________________________________________________________

So, rewrite: " ³√(m − 4) " ; as: " (m − 4) ⁽ ¹/³" ;

and rewrite: " ³√(2m + 8) " ; as: " (2m + 8) ⁽ ¹/³" ;
_________________________________________________________
And rewrite the question as:
_________________________________________________________

" (m − 4) ⁽ ¹/³ (2m + 8) ⁽ ¹/³ = 0 " ; Solve for "m" ;
_________________________________________________________

Add " (2m + 8) ¹/³ " to EACH SIDE of the equation; as follows:
_________________________________________________________

(m − 4) ¹/³⁾ − (2m + 8)¹/³ + (2m + 8) ¹/³ = 0 + (2m + 8) ¹/³ ;

to get:
_________________________________________________________

" (m − 4) ¹/³ = (2m + 8) ¹/³ " ;
_________________________________________________________

{ Note: If " x = y ⁿ ; then " x = y " .} .
_________________________________________________________ As such:

" m − 4 = 2m + 8 " ; Solve for "m" ;
_________________________________________________________

Subtract "2m" from each side of the equation; & add "4" to each side of the equation; as follows:
_________________________________________________________

m − 4 − 2m + 4 = 2m + 8 − 2m + 4 ;

to get:
_________________________________________________________

→ -1m = 12 ;

Now, divide each side of the equation by "-1 " ;
to isolation "m" on one side of the equation; & to solve for "m" ;

-1m / -1 = 12 / -1 ;
_________________________________________________________

to get:
_________________________________________________________

" m = -12 " ;

→ which is: Answer choice: [B]: " m = -12 " .
_________________________________________________________
Hope this helps!
Best wishes.
_________________________________________________________
User Nsvir
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.